2019
DOI: 10.1108/tr-04-2018-0054
|View full text |Cite
|
Sign up to set email alerts
|

Information technology competency and knowledge management in the hospitality industry service supply chain

Abstract: Purpose This study aims to provide a better understanding of how information technology (IT) competency and knowledge management (KM) contribute to service supply chain (SSC) (coordination, collaboration and efficiency) practices in the hospitality industry. Design/methodology/approach Drawing on tourism businesses, this study tests the structural relationships of IT competency, KM and SSC. Structural equation modeling is performed to test the hypotheses. A survey of 494 hotels in Iran provided empirical evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 50 publications
(54 reference statements)
0
22
0
Order By: Relevance
“…The digital revolution has had a direct influence on both travel and tourism industry (Pencarelli,2019) and contributed to the industry's supply chain (Jalilvand et al, 2019). Moreover, Big Data will continue to enhance digital technologies in tourism and hospitality (Mariani, 2020).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The digital revolution has had a direct influence on both travel and tourism industry (Pencarelli,2019) and contributed to the industry's supply chain (Jalilvand et al, 2019). Moreover, Big Data will continue to enhance digital technologies in tourism and hospitality (Mariani, 2020).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Tourism scholars and managers have acknowledged that how market information affects firm innovation (Jalilvand, Pool, Khodadadi, and Sharifi, 2019;Köseoglu, Morvillo, Altin, and Martino, 2019;Ozseker, 2019). Tourism firms update market information to support innovation and create competitive advantage (Nieves, Quintana, & Osorio, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In career clusters, the introduction of information technology will lead to the development of different professional competencies like network planning and construction management, information support Studies have shown how the introduction of information technology competency have contributed to the service supply chain practices in the hospital industry (Jalilvand et al, 2019) and performance of a firm (Ndungu et al, 2017;Pett et al, 2010;Wei & Wei, 2017). In the educational area, some researchers evaluated students' competence of information technology (IT) and recommended curricular changes (Avdeeva et al, 2017;Ni & Chen, 2016;Nwosu et al, 2018).…”
Section: Professional Competence Of Information Technologymentioning
confidence: 99%